Goode on commercial law - Goode, Royston Miles; McKendrick, Ewan (LexisNexis, 2009)
Offers coverage of commercial law in both a national and an international context. This book combines a theoretical analysis with a practical approach which examines the theory in the context of typical commercial and financial agreements, both domestic and international